Choline, DHA, and Diarrheal Disease Associated with Growth Faltering in a Case-Control Study. Issue 10 (12th September 2022) - Diaz, Jenna N; Dulience, Sherlie Jean Louis; Wolthausen, Noah; Jiang, Xuntian; Gyimah, Emmanuel; Marhône Pierre, Francesca J; Kuhlmann, F Matthew; Iannotti, Lora L
ABSTRACT: Background: Children with recurrent infectious diarrhea are susceptible to growth faltering. DHA and choline may play a role in this relationship due to their involvement in lipid metabolism, gut immunity, and inflammatory pathways. Objectives: This study aimed to characterize the contributions made by DHA and choline status and enteric damage in young children in the association between diarrheal illness and child growth. Methods: A longitudinal case-control study was conducted among children aged 6–36 mo ( N  = 195) in Cap-Haitien, Haiti. Mother-child dyads were recruited from community health posts and outpatient clinics. Cases were defined as children experiencing acute diarrhea within the last 3 d and matched to healthy controls. Child anthropometry, dietary intake, and blood and stool samples were collected at baseline and follow-up. Plasma DHA, choline, and betaine were determined by LC-MS/MS methods ( n  = 49) and intestinal fatty acid–binding protein (I-FABP) by ELISA ( n  = 183). Multivariate regression models were applied with mediation analyses to examine associations and adjust for confounding factors. Results: At baseline, mean plasma DHA concentrations (1.03 µg/mL; 95% CI: 0.91, 1.15) were not significantly different between cases and controls, nor was there a difference in mean plasma choline concentrations (4.5 µg/mL; 95% CI: 3.8, 5.1). Mean plasma I-FABP concentrations were significantly higher at follow-up in cases (3.34; 95% CI: 3.28, 3.40) than controls (3.20; 95% CI: 3.13, 3.27; P  = 0.002). In adjusted multilinear regression models, higher plasma DHA concentrations at follow-up were associated with a negative change in weight-age z score ( P  = 0.016), and follow-up I-FABP was inversely associated with height-age z score ( P  = 0.035). No interaction or mediation effects were found. Conclusions: I-FABP concentrations were significantly higher in cases as compared with controls at follow-up, suggesting ongoing enteric damage and increased risk for malnutrition. Plasma DHA and I-FABP may have a role in childhood growth outcomes.